Intelligent transport systems standards - Williams, Bob, 1947- (Artech House ITS library., 2008)
To list, summarize, and categorize intelligent transportation standards (ITS). Reviews best practices and provides listings for standards developing organizations at national and international levels. Provides guidance as to where to look in the furute to find relevant standards for ITS. Presents strategies for integrating standards in IRS planning, deployment, and operation.